Studi Katalis Ni Nano pada Material Penyimpan Hidrogen MgH2 yang Dipreparasi melalui Teknik Mechanical Alloying - Sari, Nirmala; Rahwanto, Adi; Jalil, Zulkarnain (Department of Physics, Sebelas Maret University, 2016)
The main obstacle which hinders the application of fuel cell fuels in motor vehicles today is the hydrogen storage tubes. One of the latest efforts in hydrogen storage research is to insert hydrogen in certain metals or called solid state hydrogen storage. Magnesium (Mg) is regarded as one of the material potential candidates absorbing hydrogen, because theoretically, it has the ability to absorb hydrogen in the large quantities of (7.6 wt%). This amount exceeds the minimum limit which is targeted Badan Energi Dunia (IEA), that is equal 5 wt%. However Mg has shortage, namely its kinetic reaction is very slow, it takes time to absorb hydrogen at least 60 minutes with very high operating temperatures (300-400 °C). The aim of this study is to improve the hydrogen desorption temperature hydrogen storage material based MgH2. In this method, milling of material is done in the time of 10 h with the variation of catalyst inserts a for 6wt%, 10wt% and 12 wt%. The results from XRD measurements in mind that the sample was reduced to scale nanocrystal. Phase that appears of the observation of result XRD is MgH2 phase as the main phase, and followed by Ni phase as minor phase. The result of observations with DSC, to the lowest temperature obtained on the sample with a weight of catalyst 12 wt% Ni catalyst that is equal to 376 °C. These results successfully repair pure temperature of Mg-based hydrides.